MORFOMETRIK IKAN TAPAH (Wallago leeri Bleeker, 1851) DARI SUNGAI SIAK DAN SUNGAI KANDIS PROVINSI RIAU - N. Nathasya; R. Elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The study about morphometric of tapah fish (Wallago leeri Bleeker, 1851) from Siak Riverand Kandis River had been done. The purpose of this study was to compare tapah fish fromSiak River and Kandis River using 26 morphometric characters. This study was carried outfrom February 2013 to July 2013 using survey method. The number of samples whichcollected was 60 individual of tapah fish, consisted of 30 tapah fish from Siak River and 30tapah fish from Kandis River. The results indicated the differences of morphometriccharacters between tapah fish from Siak River and Kandis River. Linear regression analysisshowed that tapah fish from Siak River and Kandis River have very weak to very strongrelationship. Its growth status showed the positive allometric, isometric, and negativeallometric.